The Relationship Between Internet Addiction, Internet Gaming And Anxiety Among Medical Students In A Malaysian Public University During Covid-19 Pandemic - Nurazah Ismail; Ahmad Izzat Bin Ahmad Tajjudin; Hafiz Jaafar; Nik Ruzyanei Nik Jaafar; Azlin Baharudin; Normala Ibrahim (MDPI, 2024)
Indexed by WOS/SCOPUS/ERA